SELF-ASSESSMENT OF OPERATING THEATRE NURSE COMPETENCE IN PERIOPERATIVE CARE - Ābele, Ilona; Vīksna, Laura; Gulbe, Dagnija; Skuja-Petruševiča, Līga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Assessment of competence level of operating theatre nurses (OTN) has a significant role in ensuring patient safety, continuity of perioperative care, and positive care environment, allowing to identify shortcomings and address them. The competence level describes quantitatively the competence in perioperative care — a set of skills, attitudes, and knowledge required for effective and safe perioperative care. A simple method to assess the competence level is a self-assessment scale; however, this method has not been used in Latvia to establish the OTN competence levelThe goal of this work is to determine the perceived level of competence in the perioperative care of OTN in a multi-profile hospital in Latvia. For this purpose, a modified perioperative competence self-assessment scale was used, based on Gillespie’s (2012) Perceived Perioperative Competence Scale-Revised (PPCS-R). The results show that OTN have a high perceived level of competence. However, the leadership subscale (which includes coordination and management) displayed lower levels of perceived competence, which shows the insufficiency of training. The results also show that certified OTN, those with more work experience, and OTN with a Bachelor’s degree have a higher perceived competence level. The scale adapted to Latvian exhibits equally good internal consistency as other versions of PPCS-R.